Figury dzieciństwa w militarystycznym dyskursie w Związku Radzieckim i we współczesnej Rosji - Wojciech Siegień (Problemy Wczesnej Edukacji)
The article presents the use of childhood figures in the process of constructing a militaristic discourse in Russian society. The author also tries to identify ways to use similar figures of childhood in different historical and political contexts. Comparative analysis was related to the figures taken from the reality of the Soviet Union and modern Russia. The method of analysis was based on a narrative analysis. Analysing propaganda broadcasts at the syntactic and paradigmatic level, the paper shows that propaganda texts created in different times use similar measures plots distant in time use similar measures. The use of figures of childhood appears to be the one of the most effective tools of military propaganda in Russia.